The Relationship Between Inter-Dialytic Weight Gain (IDWG) and Post-Dialysis Blood Pressure Changes in Hemodialysis Patients at Prof. Dr. Margono Sookarjo Hospital - Gusti Rama Dwitiya; Adityawarman Adityawarman; Octavia Permata Sari (International Journal of Health Engineering and Technology, 2026)
Chronic Kidney Disease (CKD) is a progressive chronic disease that may damage the function of kidneys and affect the stability of fluids and electrolytes in our body that will impact on our body’s system. A usual alternative therapy that has been done to CKD’s patients is Hemodialysis (HD). Inter-Dialytic Weight Gain (IDWG) is an increase in volume which is manifested by an increase in body weight as a basis for discovering the amount of incoming fluids within interdialytic process. IDWG and changes in post dialysis blood pressure are closely related to each other because in hemodialysis process, there is a diffusion exchange of dialysis fluids and dirty fluids in patient’s body so that it may provide clinical manifestations of blood pressures’ changes after hemodialysis process. To discover the relationship between Inter-Dialytic Weight Gain (IDWG) and the changes in post dialysis blood pressure among hemodialysis patients at Prof. Dr. Margono Soekarjo Regional Public Hospital. This research is an analytic observational research and using cross sectional approach. Sampling method with purposive sampling by the amount of 41 patients, and then the results were analyzed for its significance by using Somers’D test. The result of Somers’D test to discover the significance between variables were resulting in p value = 0,000(p<0,05) dan r = 0,746 for the relationship between IDWG and Changes in Post Dialysis Blood Pressure. There is a relationship between Inter-Dialytic Weight Gain and changes in post dialysis blood pressure among hemodialysis patients at Prof. Dr. Margono Soekarjo Regional Public Hospital, Purwokerto.